E-Module Learning for Scaling Serious Illness Communication Skills Teaching: A Pilot Study in Family Medicine and Palliative Care - Helen James; Paul Krueger; Daphna Grossman; Warren Lewin (Palliative Medicine Reports)
Background: Serious illness communication (SIC) competency is essential for health care professionals. However, many clinicians receive little-to-no SIC training, and there is little evidence as to which teaching method is most feasible to incorporate into postgraduate curricula. Two e-modules were created to adapt high-yield knowledge to deliver asynchronous, time-efficient, standardized communication skills teaching. This project evaluated SIC e-module teaching feasibility, learner and faculty perceptions toward e-module learning on this topic, as well as learner confidence and skill usage post-completion. Methods: Family Medicine residents and palliative care fellows from two training sites were invited to asynchronously complete the e-modules on their own time and complete a survey to assess attitudes, perceptions, and needs toward them and impact on SIC skills immediately and 1-month post-completion. Faculty from the main site were also invited to view the e-modules and complete a survey immediately afterward assessing attitudes, perceptions, and feasibility on SIC e-module learning. Results: In total, 19/50 (38%) learners completed the e-modules and post-training survey and 14/19 (73%) of those learners completed the 1-month follow-up survey. In total, 13/60 (22%) faculty completed the survey. Participants liked the structure and design of the e-modules and felt they were appropriate for their learners’ level of training, were effective, time-efficient, and provided relevant SIC information. Case-based video demonstrations were identified as the most useful teaching method. Most learners intended to use new skills in clinical practice, rewatched both e-modules within 1 month of initial viewing, and reported using learned skills in practice. Conclusion: E-module training provides a standardized method to scale postgraduate SIC skills teaching asynchronously and was well liked by learners and faculty. Barriers exist to completing them outside of a core curriculum. Early data suggest e-modules can be used iteratively and further research is needed to determine how their use impacts communication confidence and competency.